The Perceptions of ESP Students' Target Needs: A Case Study. (2nd June 2015) - Kazar, Sevda Gul; Mede, Enisa
Abstract: The purpose of this study is to identify the target needs of the students engaged in an ESP program offered by the Faculty of Fine Arts at a private university in Turkey. A sample of eighty-four students (N=84) participated in this study. The quantitative data were obtained through a pre-needs analysis questionnaire, and the qualitative data were collected from a semi-structured interview related to the perceptions of the students' target needs. The findings of the study revealed that the ESP program should focus on the effective use of language strategies in given tasks such as improving presentation skills, learning key terms, writing email messages, and reading academic texts.